ThinSight: A new interaction technology for ubicomp - Hodges, Steve; Izadi, Shahram; Butler, Alex; Rrustemi, Alban (In Adjunct proceedings of 9th international Conference on Ubiquitous Computing, 2007)
We present a novel technology suitable for situated displays, called ThinSight. It combines up close zero-force multi-touch interaction, with interaction and data exchange from a distance using a mobile device. The novelty of ThinSight lies both in the combination of these features and in the thin form-factor of the hardware which can be fully integrated into commercially available LCDs without affecting display quality. This readily deployable situated display technology opens up many new ubiquitous computing possibilities.